Hip displacement in Wolf–Hirschhorn syndrome: Report on three cases and review of associated musculoskeletal pathologies. Issue 6 (7th April 2020) - Buddhdev, Pranai K.; Sabir, Ataf; Kokkinakis, Michailis; Irving, Melita; Norman‐Taylor, Fabian
Abstract: Wolf–Hirschhorn syndrome is a rare genetic disease caused by a chromosomal deletion of the distal short arm of Chromosome 4. It is associated with multisystem abnormalities, including delayed growth, characteristic facial features, epilepsy, and skeletal abnormalities. We report three patients who developed hip displacement, and describe the occurrence of delayed and nonunion in patients who underwent corrective proximal femoral osteotomy for hip displacement. We also performed a literature review identifying common musculoskeletal presentations associated with the condition. Patients with Wolf–Hirschhorn Syndrome are at risk of hip displacement (subluxation), and we would advocate annual hip surveillance in this patient group.